Negative impact of benign prostatic hyperplasia on fertility in dogs–a mini-review - Anna Domosławska-Wyderska; Sławomir Zduńczyk; Agata Rafalska (Frontiers in Veterinary Science)
The aim of this article is to provide a comprehensive review of the negative impact of benign prostatic hyperplasia (BPH) on fertility in dogs. BPH is the most common disease of the prostate gland and one of the major causes of infertility in dogs, associated with impaired semen quality. Hormonal imbalance, oxidative stress, biochemical changes in prostatic fluid and haematospermia have been discussed as causes of reduced semen quality in dogs with BPH. Chronic prostatitis often occurs concurrently with BPH and has an additive negative effect on semen quality and fertility. In breeding dogs with infertility associated with BPH, treatment with the anti-androgen osaterone acetate or the 5α-reductase inhibitor finasteride is recommended to reduce prostate size and clinical symptoms and to restore fertility. Combined occurrence of BPH and chronic prostatitis requires simultaneous treatment of both conditions, including microbials with good penetration into the prostate. The use of antioxidants in the supportive treatment of BPH seems reasonable.